Digital audio watermaking techniques and technologies applications and benchmarks - Cvejic, Nedeljko; Seppanen, Tapio (Information Science Reference, 2008)
"Digital audio watermarking has been proposed as a new and alternative method to enforce intellectual property rights and protect digital audio from tampering. This composition of theoretical frameworks, recent research findings, and practical applications will benefit researchers and students in electrical engineering and information technology, as well as professionals working in digital audio"--Provided by publisher